A Case of Lance-Adams Syndrome with Mixed Cortical and Reticular Reflex Myoclonus. Issue 1 (18th March 2022) - Chan, Andy Ho Wing; Nichols, Jamie; Tse, Winona; Ryan, Sophia L.
Background: Lance Adams syndrome is a chronic post-hypoxic myoclonus. Phenomenology Shown: This video abstract illustrates Lance Adams Syndrome with mixed cortical and reticular reflex myoclonus in a 32-year-old woman following respiratory arrest in the setting of an asthma attack, as well as improvement in her exam following pharmacologic management. Educational Value: Lance Adams syndrome can include both cortical and reticular reflex myoclonus features while interdisciplinary intervention and pharmacological treatment can improve symptomatology.